Dynamics of the Implementation of the Papua Province Bureaucratic Reform Agenda - Yosephina Ohoiwutun (Formosa Journal of Applied Sciences, 2023)
This study aims to look at the implementation of bureaucratic reform in Papua Province in the context of realizing good governance. As part of this type of qualitative research, this research uses library research. Data were obtained from various library sources that are relevant to the topic being discussed. Data analysis was carried out through data reduction, data presentation, and drawing final conclusions. The results of this study indicate that the Provincial Government of Papua has attempted to realize better Governance, through continuous improvement marked by an increase in value on the fulfillment and reform aspects, and followed by an increase in value on the total component results.